Risk Factors Associated with Ninety Day Readmission in Chronic Obstructive Pulmonary Disease Exacerbation at a Tertiary Care Hospital: A retrospective cohort study - Pant, P.; Joshi, A. (Kathmandu University Medical Journal, 2020)
Background Chronic obstructive pulmonary disease (COPD) exacerbation is a leading cause of frequent hospital admission. Globally, several studies have reported potential risk factors associated with COPD exacerbations which are largely unknown in Nepalese health care setting. Objective To identify the risk factors associated with hospital readmission within ninety days of discharge in acute COPD exacerbation. Method This is a hospital based retrospective cohort study conducted at Tribhuvan University Teaching Hospital. COPD patients admitted in respiratory ward from August 2019 to November 2019 were followed up till 90 days after discharge. Logistic regression analysis was performed at 95% Confidence Interval (CI) to identify risk factors for readmission in COPD exacerbation. Statistical analysis was performed using SPSS version 20.0. Result Of total 86 patients hospitalized for COPD, 42 (48.8%) had at least one subsequent readmission during post-discharge follow-up period of 90 days. Mean age of patients was 70.55±10.98 years. There were 45 (52.3%) males. Logistic regression analysis revealed preadmission domiciliary oxygen use (Odds Ratio (OR) 2.93; 95% CI 1.195- 7.202; p=0.019), admission in intensive care unit (ICU) (OR 3.060; 95% CI 1.145- 8.179; p=0.026), previous hospital admission for COPD exacerbation (OR 3.230; 95% CI 1.219-8.556; p=0.018), age (OR 0.946; 95% CI 0.905-0.988; p=0.012) and duration of hospital stay (OR 0.901; 95% CI 0.819-0.992; p=0.034) were independently associated with ninety day readmission in COPD patients. Conclusion Five clinical factors were found to be independently associated with COPD readmission in this study. Large multi-centre study at various health care levels is recommended to validate the potential risk factors in different populations and health care settings in Nepal.